Diversity in Habitat Use by White Sturgeon Revealed Using Fin Ray Geochemistry - Sellheim, Kirsten; Willmes, Malte; Lewis, Levi S.; Sweeney, Jamie; Merz, Joseph; Hobbs, James A. (Frontiers in Marine Science, 2022)
Understanding life-history diversity in a population is imperative to developing effective fisheries management and conservation practices, particularly in degraded environments with high environmental variability. Here, we examined variation in habitat use and migration patterns of White Sturgeon (Acipenser transmontanus), a long-lived migratory fish that is native to the San Francisco Estuary, CA, USA. Annual increment profiles were combined with respective geochemical (87Sr/86Sr) profiles in sturgeon fin rays to reconstruct annual salinity chronologies for 112 individuals from 5-30 years old. Results indicated a complex and diverse amphidromous life history across individuals, characterized largely by estuarine residence, a general ontogenetic trend toward higher-salinity brackish habitats, and high variability in habitat use across all age groups. Hierarchical clustering based on fin ray geochemistry during the first 10 years of life, prior to sexual maturation, indicated at least four distinct migratory phenotypes which differed largely in the timing and duration of juvenile to subadult movements between fresh- and brackish-water habitats. This study provides information regarding habitat use and migration in sub-adult fish that was previously lacking. Different migratory phenotypes vary in exposure to stressors across time and space and populations. Understanding White Sturgeon habitat distributions through space and time at different life stages can help identify areas where habitat restoration would be most effective and develop management actions to reduce stressors associated with specific areas where White Sturgeon are present.